Neurosurgery for Refractory Schizophrenia: A Systematic Literature Review - Almeida, Bruna Veronese; Aquino, Isadora Profírio; Silva, Ledismar José (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Schizophrenia is a chronic and disabling psychiatric disease that can be refractory to conventional treatment. The present study aims to gather information about the circuitry related to schizophrenia to describe possible surgical targets, and to establish whether psychosurgery can be a safe and effective treatment option for refractory schizophrenia. A systematic review of the literature was conducted and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. An electronic search was performed in the Pubmed and BVSalud databases using medical subject headings (MeSH) combined with Boolean operators. Out of the 724 studies retrieved, 13 were included in the review. Regarding leucotomy without a stereotactic approach, we found side effects such as irritability, nervous excitement, cases of disinhibition, and compromised normal social control. In other stereotactic procedures, there was some improvement, mainly regarding aggressiveness and positive symptoms; an anterior capsulotomy had an efficacy rate of 74% according to the Clinical Global Impression (CGI) rating scales. The only deep brain stimulation (DBS) case report found in our study described a significant improvement in the positive and negative symptoms. The use of a stereotactic approach enables psychosurgery to be a safe and effective treatment option in cases of refractory schizophrenia, improving the quality of life and the symptoms. Cognitive and negative symptoms remain a challenge in the treatment of schizophrenia, revealing that more targets in the circuitry must be surgically explored. Furthermore, more clinical trials are needed to compare these many surgical techniques and targets, using a standard evaluation parameter. The results show that DBS has a promising future in the treatment of refractory schizophrenia.
Keywords: schizophrenia; psychosurgery; ablation techniques; deep brain stimulation; neurosurgery